Cynomolgus monkeys (Macaca fascicularis) experimentally infected with B19V and hepatitis A virus: no evidence of the co-infection as a cause of acute liver failure - Luciane Almeida Amado Leon; Renato Sergio Marchevsky; Ana Maria Coimbra Gaspar; Rita de Cassia Nasser Cubel Garcia; Adilson José de Almeida; Marcelo Pelajo-Machado; Tatiana Xavier de Castro; Jussara Pereira do Nascimento; Kevin E Brown; Marcelo Alves Pinto (Memorias do Instituto Oswaldo Cruz, 2016)
This study was conducted to analyse the course and the outcome of the liver disease in the co-infected animals in order to evaluate a possible synergic effect of human parvovirus B19 (B19V) and hepatitis A virus (HAV) co-infection. Nine adult cynomolgus monkeys were inoculated with serum obtained from a fatal case of B19V infection and/or a faecal suspension of acute HAV. The presence of specific antibodies to HAV and B19V, liver enzyme levels, viraemia, haematological changes, and necroinflammatory liver lesions were used for monitoring the infections. Seroconversion was confirmed in all infected groups. A similar pattern of B19V infection to human disease was observed, which was characterised by high and persistent viraemia in association with reticulocytopenia and mild to moderate anaemia during the period of investigation (59 days). Additionally, the intranuclear inclusion bodies were observed in pro-erythroblast cell from an infected cynomolgus and B19V Ag in hepatocytes. The erythroid hypoplasia and decrease in lymphocyte counts were more evident in the co-infected group. The present results demonstrated, for the first time, the susceptibility of cynomolgus to B19V infection, but it did not show a worsening of liver histopathology in the co-infected group.